PENGEMBANGAN MODEL KONSTITUTIF BETON MUTU TINGGI PADA KONDISI PEMBEBANAN MULTIAKSIAL - Made Mulia Gunawan, I
Abstrak : This research presents the development of a constitutive model capable of accurately modelling the behaviour of high-strength concrete. The constitutive model is derived within the plasticity theory including assosiative, nonassosiative, nonlinear strain hardening and softening. This model is then implemented in finite element program. Material parameters, which are used in this model, are established by experimental data reported from uniaxial and triaxial test programs in the previous research. The model is then compared to the experimental result. In general, the model shows good result. On the other hand, the result of this study indicates that at high lateral stress, the stress-strain curve from experimental result tends to follow nonassosiative flow rule, while at low lateral stress it follows assosiative flow rule.Kata kunci : model konstitutif, beton mutu tinggi, plastisitas, assosiative, nonassosiative.